Implikasi Nilai Manusia dalam Praksis Kepemimpinan Menurut Kejadian 1:26-27 - Perangin Angin, Yakub Hendrawan; Yeniretnowati, Tri Astuti; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi IKAT Jakarta, 2020)
The implementation of human values in leadership praxis based on the Book of Genesis 1: 26-27 is raised because of various phenomena that have occurred in which many people are treated inhumanely. The analysis was carried out by means of a literature review, by analyzing the leadership practices that occur both in general and Christian circles. The main sources of analysis are several relevant sources, including research results contained in journals and books. All of these sources were analyzed by looking at the relationship and compatibility with the title of this paper. So it can be concluded that his leadership can describe how the leader's view of humans,